(untitled) (Jurnal Bina Praja, 2025)
The Special Economic Zone (SEZ) in Galang Batang, Bintan Regency, Indonesia, plays a crucial role in regional economic development by leveraging the area’s strategic location and natural resources. The purpose of this study is to examine the collaborative governance model employed in managing the Galang Batang SEZ, focusing on the challenges and factors influencing the collaboration between various stakeholders, including government bodies and business entities. This study used a qualitative descriptive research approach; both secondary and primary data were gathered to analyze the existing conditions within the SEZ. Data analysis involved pattern matching, explanation development, and the construction of logical models to provide a comprehensive understanding of the governance processes. The results indicate that while there is an effort to coordinate between stakeholders, challenges remain in integrating services and ensuring effective collaboration due to overlapping functions within the One Stop Investment and Integrated Services Office. Despite these challenges, the study highlights the importance of cooperative leadership and the role of the local government in supporting the SEZ’s operations. The findings suggest that addressing institutional fragmentation and enhancing human resource development are critical to improving the efficiency and success of the governance model. In conclusion, while the current collaborative governance structure in the Galang Batang SEZ faces operational hurdles, improvements in service delivery and inter-institutional coordination are essential to realize the full potential of this economic initiative.